Using high pressure to understand the behavior of organic molecular crystals - María Guadalupe Vasquez-Ríos (IUCrJ)
In the recent publication by Zhou et al. [(2025). IUCrJ, 12, 16–22], the crystal structure of benzo[a]pyrene was studied under high pressure up to 28 GPa using single-crystal X-ray diffraction and DFT calculations. This commentary highlights the importance of high pressure for analyzing organic molecular crystals.